2022
DOI: 10.1177/15579883221084798
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Chronic Periodontal Disease and Erectile Dysfunction: A Case–Control Study

Abstract: Erectile dysfunction (ED) and chronic periodontal disease (CPD) share mutual risk factors, and the incidence of ED is increasing among young adults. The relation of CPD and ED remains obscure due to inconsistent clinical evidence. This study aimed to further assess the relationship between CPD and ED using the Community Periodontal Index of Treatment Need (CPITN) and the International Index of Erectile Function (IIEF). Totally, 202 adult men were included, with 100 subjects with ED in the case group and 102 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…But, the increased risk of endothelial dysfunction has been associated with high levels of inflammatory mediators such as interleukin (IL)-6, IL-8, tumor necrosis factor-alpha (TNF-α), and IL-1. [121][122][123] TNF-α has been reported to play a key role in the induction of endothelial dysfunction. 124,125 Multiple studies have reported a reduction in TNF-α levels after successful periodontal treatment, and it is evident that significantly higher plasma levels of TNF-α were associated with moderate to severe ED owing to their known effects on the vasculature.…”
Section: Erectile Dysfunction (Ed)mentioning
confidence: 99%
“…But, the increased risk of endothelial dysfunction has been associated with high levels of inflammatory mediators such as interleukin (IL)-6, IL-8, tumor necrosis factor-alpha (TNF-α), and IL-1. [121][122][123] TNF-α has been reported to play a key role in the induction of endothelial dysfunction. 124,125 Multiple studies have reported a reduction in TNF-α levels after successful periodontal treatment, and it is evident that significantly higher plasma levels of TNF-α were associated with moderate to severe ED owing to their known effects on the vasculature.…”
Section: Erectile Dysfunction (Ed)mentioning
confidence: 99%